2013
DOI: 10.1073/pnas.1221068110
|View full text |Cite
|
Sign up to set email alerts
|

Half or more of the somatic mutations in cancers of self-renewing tissues originate prior to tumor initiation

Abstract: Although it has been hypothesized that some of the somatic mutations found in tumors may occur before tumor initiation, there is little experimental or conceptual data on this topic. To gain insights into this fundamental issue, we formulated a mathematical model for the evolution of somatic mutations in which all relevant phases of a tissue’s history are considered. The model makes the prediction, validated by our empirical findings, that the number of somatic mutations in tumors of self-renewing tissues is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
364
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(400 citation statements)
references
References 25 publications
30
364
4
2
Order By: Relevance
“…Colonic stem cells divide very frequently-every 30 h by some estimates (35)-and would therefore be expected to accumulate large numbers of founder mutations over the years, with total mutational burden increasing with age. Recent studies show a correlation between age at diagnosis and total number of somatic mutations in acute myeloid leukemia (36) and colorectal cancer (20,37). We tested this correlation in our data after excluding MSI cases, as a distinct mutational mechanism is operational in these tumors.…”
Section: Resultsmentioning
confidence: 95%
“…Colonic stem cells divide very frequently-every 30 h by some estimates (35)-and would therefore be expected to accumulate large numbers of founder mutations over the years, with total mutational burden increasing with age. Recent studies show a correlation between age at diagnosis and total number of somatic mutations in acute myeloid leukemia (36) and colorectal cancer (20,37). We tested this correlation in our data after excluding MSI cases, as a distinct mutational mechanism is operational in these tumors.…”
Section: Resultsmentioning
confidence: 95%
“…Recent work has shown that a very large proportion of mutations may have appeared before tumour initiation and that the number of somatic mutations in tumours of self-renewing tissues are positively correlated with the age of the patient at diagnosis 11,12 . In support of that, we see a trend that younger patients below the age of 55 (N ¼ 15/49) in our cohort tend to have much smaller number of mutations (2.16 vs 3.88 mutations per Mb; P ¼ 0.018).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, next-generation DNA and RNA sequencing efforts (eg, The Cancer Genome Atlas) have demonstrated that very few common mutations unite particular solid tumor types; rather, patient tumors have a spectrum of mutations that collectively drive tumor growth. 11,33,34 In the face of this rapidly emerging and previously unappreciated complexity, it is not surprising that therapeutics developed using overly simplistic paradigms and models have been only modestly successful at impacting survival. The development of personalized medicine and its efficient implementation will likely leverage PDX models, the CSC paradigm and next-generation DNA and RNA sequencing to improve our collective understanding of tumor pathobiology, beginning with the more precise identification of patient subtypes and the identity of CSC in each of these respective tumor subtypes.…”
Section: Addressing Tumor Heterogeneitymentioning
confidence: 99%
“…As previously discussed, the Cancer Genome Atlas project has demonstrated that the spectrum of driver mutations differs significantly among patients, thus the relevance of particular GEMMs to patients in the clinic is increasingly questionable. 33,34 Notwithstanding the above criticisms, GEMMs may have advantages over xenograft models in their cellular composition and/or sensitivity to therapeutic agents. 48 Specifically, GEMM tumors contain stromal and hematopoietic components not possible in a human tumor xenograft setting, and thus these tumors may respond more appropriately to small molecules, immunomodulatory, and/or biological agents that cross-react with mouse antigens.…”
Section: Traditional Models Have Not Predicted Clinical Successmentioning
confidence: 99%
See 1 more Smart Citation